(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Sorption properties of sorbents on silica–manganese(II) oxide binary systems base have been evaluated by means of conductometry method. The influence of different factors (particularly the influence of pH values during the precipitation of manganese oxide and silica gel) on sorption properties of such systems has been discussed. The role of thermal treatment on sorption properties has been studied as well. It has been revealed that definite most optimal values for thermal treatment temperature exist, which lead to the sorbents characterized by higher adsorption capacity.